Current trends in biodiesel production technologies and future progressions: A possible displacement of the petro-diesel. (10th October 2022) - Akram, Fatima; Haq, Ikram ul; Raja, Saleha Ibadat; Mir, Azka Shahzad; Qureshi, Sumbal Sajid; Aqeel, Amna; Shah, Fatima Iftikhar
Abstract: The rising energy demand of the world due to rapidly expanding population and accelerated industrialization is primarily satisfied by non-renewable fossil fuels. Fossil fuels are depleting at a faster rate and their overexploitation has raised serious environmental concerns which necessitate switching to alternative sustainable energy resources. Biodiesel has caught substantial interest as a viable and adaptable fuel substitute to the currently employed nonrenewable fuels due to its renewability, biodegradability and environmentally benign nature. Biodiesel can be derived from multiple sources by different production processes among which transesterification is the most widely exploited process. This article reviews different feedstocks for biodiesel production and strategies to improve lipid content in microalgae for enhanced biodiesel production. This review further describes biodiesel production methods, types of catalyst used in transesterification process, and assesses the recent critical challenges along with technical solutions for sustainable biodiesel production. Graphical abstract: Image 1 Highlights: Importance of biodiesel as a sustainable renewable energy is reviewed. Potential feedstocks for biodiesel production are discussed. Used strategies to improve lipid yield from microalgae for biodiesel production. Methodologies employed for biodiesel production are portrayed. Application of different catalysts in biodiesel production is elucidated.